Pertanggungjawaban Hukum Pemilik Ternak Akibat Ternak Yang Merusak Tanaman Orang Lain - Lahmuddin Zuhri; Rabiatul Munawarah; Hanuring Ayu Ardhani Putri; Firstnandiar Glica Aini Suniaprily (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The problem of livestock roaming freely in Kerato Village, Unter Iwes District, has caused damage to property and agricultural land, social conflict, and economic losses. To address this problem, the Kerato Village Government issued Kerato Village Regulation Number 7 of 2021. This regulation stipulates administrative sanctions in the form of fines and compensation. This study uses an empirical legal research approach, a method that analyzes social phenomena in society using legislative, sociological, comparative, and case studies. The results show that the legal liability of livestock owners, according to Kerato Village Regulation Number 7 of 2021 concerning Livestock Maintenance, stipulates that owners of livestock that roam freely and damage agricultural land will be subject to administrative sanctions in the form of fines for security costs and maintenance costs for the secured livestock, and are required to pay compensation for crop damage. The results of the study, related to Islamic law, emphasize the responsibility of livestock owners based on the principle of justice, requiring balanced compensation, and encouraging dispute resolution through mediation